1997
DOI: 10.1093/jpepsy/22.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Body Image and Psychosocial Adjustment in Adolescent Cancer Survivors

Abstract: Examined body image and social adjustment in 21 adolescents who had completed cancer treatment and a healthy comparison group. Subjects completed questionnaires assessing body image and social adjustment and were videotaped during an interview. Raters blind to health status independently rated subjects' attractiveness. Cancer survivors reported less than half as many social activities as the healthy controls. No group differences were found on social anxiety, loneliness, or composite body image scores. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
121
0
5

Year Published

1999
1999
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(132 citation statements)
references
References 29 publications
6
121
0
5
Order By: Relevance
“…32 Men in particular, in this study, are well below the general population both in height and weight (Table 3). Pendley et al 33 found that young persons with longer post-cancer treatment times reported a more negative body image, and problems can arise long after treatment has ended. 32,34 Most adults in our study group, however, had a predominantly positive self-image.…”
Section: Discussionmentioning
confidence: 99%
“…32 Men in particular, in this study, are well below the general population both in height and weight (Table 3). Pendley et al 33 found that young persons with longer post-cancer treatment times reported a more negative body image, and problems can arise long after treatment has ended. 32,34 Most adults in our study group, however, had a predominantly positive self-image.…”
Section: Discussionmentioning
confidence: 99%
“…Many young adult survivors of cancer have reported disruption to their extracurricular activities at school, 20 and this interruption may have put their social development at risk. 17 Survivors have been found to be more socially isolated, 21 and they do not participate in as many peer activities, such as going out with friends, as those who were never-ill. 22 It has been suggested that friendships during childhood and adolescence are important for later sexual relationships. 23 Mental retardation was strongly related to likelihood and rate of marriage, in that those affected had a rate of marriage nine times less than that seen among survivors not affected by this condition.…”
Section: Synthesis Of Internal Comparisonsmentioning
confidence: 99%
“…age and diagnosis). 22 Pendley et al 26 found that the longer the adolescents were off treatment, the more they perceived problems related to self-worth, social anxiety, and greater negative perceptions of body image (although observers did not rate them as less attractive). Reasons for this change in self-perception over time by such survivors have been debated: Is it that the patient's problems are truly becoming worse over time, or was the patient in an 'adaptive-denial' mode of coping with his/her problems during treatment?…”
Section: Psychological/emotional Factorsmentioning
confidence: 99%